Prime Minister’s Decree No. 2482 of the Year 2025 - Prime Minister (The Middle East Library For Economic Services, 2025)
Article-1 The text of article-148 of the executive regulations of the Capital Market Law, referred to, shall be replaced with the following text: Article-148: The private equity funds and the real estate investment funds of private offerings may issue certificates that the value of which is paid in instalments, provided that the information memorandum shall state the method of payment of the value of the certificate instalments and the consequences of payment default subject to the provisions stipulated in article (148-bis) of these regulations.